708 A 360 Degree Exploration of Key Factors in Consent in Aortic Aneurysm Repair. (12th October 2021) - Rolls, A; Guni, A; Sharp, B; Rajgopal, A; Normahani, P; Jenkins, M; Jaffer, U
Abstract: Introduction: Shared decision making is the gold standard for treatment decisions. Although there is an evidence base to recommend either open surgical repair or endovascular repair (EVAR) for patients with abdominal aortic aneurysms (AAA) based on individual outcome factors, there is scope for choice depending on subjective factors. This study aims to identify key factors to be addressed in the consent process using a 360-degree exploration. Method: A literature search conducted on Medline and Embase databases identified 13 key factors, which were formulated into questions with five-point Likert scales. Seven vascular surgeons, two interventional radiologists, two vascular anaesthetists, two intensivists, one vascular physician, and five patients who underwent either open surgical repair or EVAR were interviewed in a semi-structured manner. Descriptive statistical analysis was performed to identify the importance of each factor. Results: The most important factors for clinicians and patients were "pre-existing medical conditions" and "risk of post-operative complications". The least important factors were "need for follow-up appointments" and "post-operative pain". Patients placed the most importance on "type of anaesthetic used", and relatively less importance on "length of hospital stay" and "probability of admission to ICU". Analysis of free-flowing answers yielded another 14 factors. Factors were grouped into "surgical focus", "medical and perioperative focus" and "patients and communication". Conclusions: There is heterogeneity in the importance given to factors between clinicians and patients. The factors identified from this 360-degree assessment should be integrated into formal topics of discussion in the consent process to support patients in making informed decisions regarding AAA treatment.